2015
DOI: 10.1038/npp.2015.204
|View full text |Cite
|
Sign up to set email alerts
|

The Neuro-Environmental Loop of Plasticity: A Cross-Species Analysis of Parental Effects on Emotion Circuitry Development Following Typical and Adverse Caregiving

Abstract: Early experiences critically shape the structure and function of the brain. Perturbations in typical/species-expected early experiences are known to have profound neural effects, especially in regions important for emotional responding. Parental care is one species-expected stimulus that plays a fundamental role in the development of emotion neurocircuitry. Emerging evidence across species suggests that phasic variation in parental presence during the sensitive period of childhood affects the recruitment of em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
215
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 233 publications
(234 citation statements)
references
References 161 publications
(183 reference statements)
14
215
0
5
Order By: Relevance
“…Specifically, it may be adaptive to move from a state of parent-regulation to self-regulation earlier in environments characterized by absent or inconsistent parental care. Put another way, the quantity and quality of parental care may act as an environmental signal for the pace of offspring maturation within circumscribed emotion systems [8, 41]. …”
Section: The Stress Acceleration Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it may be adaptive to move from a state of parent-regulation to self-regulation earlier in environments characterized by absent or inconsistent parental care. Put another way, the quantity and quality of parental care may act as an environmental signal for the pace of offspring maturation within circumscribed emotion systems [8, 41]. …”
Section: The Stress Acceleration Hypothesismentioning
confidence: 99%
“…Also, a prolonged period of cortical development is associated with greater general intelligence [43]. In terms of emotion circuitry, we have recently suggested that a period of immaturity is required so that parent-assisted emotion regulation can help mold the circuitry into its stable adult state [41]. In this hypothesis, early termination of the immature period would shift the circuit into a stable state of function before it had acquired the characteristics needed for adequate self-regulatory control.…”
Section: The Stress Acceleration Hypothesismentioning
confidence: 99%
“…The next section examines developmental psychopathology, with an initial chapter by Boyce focusing on biology-environment interactions in disease pathogenesis (Boyce, 2016). Nim Tottenham's group has spent years examining the effects of developmental studies of stress on the brain, in particular through an amazing series of studies with children who were raised in situations of social neglect (Callaghan and Tottenham, 2016). Johanna Bick and Charles Nelson then provide further exploration of these topics and mechanisms by examining the developmental consequences of toxic stress exposure (Bick and Nelson, 2016).…”
mentioning
confidence: 99%
“…It is hypothesized that these limitations in an extremely important period for child development, combined with limited access to materials and suitable conditions for the development of the child, could not be compensated for up to school age for this study's sample. It has been pointed out also the need to deepen the study of environmental variables (Lipina & Segretin, 2015), as other factors such as language environment at home (Melvin et al, 2016), absence of a parent (McLanahan et al 2013), or stress as a result of living in disadvantaged environments (Callaghan & Tottenham, 2016;Evans & Fuller-Rowell, 2013;Piccolo et al, 2016) may have short-and long-term effects in child development. One can ask: if all children are from low SES environments, why do some of them have presented deficits but some of them have not?…”
Section: Discussionmentioning
confidence: 99%